Biomimics of phenazine oxidase activity of a cobalt (III)‐dipyridylamine complex: Spectroscopic, structural, and computational studies. (20th October 2021) - Mahato, Rajani Kanta; Das, Soumik; Joshi, Mayank; Choudhury, Angshuman Roy; Misra, Anirban; Biswas, Bhaskar
Abstract: This manuscript demonstrates the synthesis, structural characterization, computational studies, and biomimics of the phenazine oxidase activity of a newly designed cobalt (III) complex, [Co (dpa)(dpa‐H + )(N3 )2 ]Cl2 (1 ) [dpa = 2, 2′‐dipyridylamine] under an aerobic condition. The crystal structure analysis reveals that the cobalt (III) center adopts an octahedral geometry, and the complex forms a beautiful supramolecular framework through noncovalent interactions. The cobalt (III) catalyst turns out to be a promising catalyst for the oxidative coupling of o ‐phenylenediamine (OPD) in oxygen‐saturated methanol with an excellent turnover number, k cat  = 7.85 × 10 3  h −1 . Spectrophotometric, electrochemical, mass spectrometry, and computational analysis ensure that the course of catalysis undergoes through a catalyst‐substrate complexation, facilitating the development of cobalt‐iminobenzoquinone species in the solution. The computational calculations employing the density functional theory (DFT) throw a light to the mechanistic insights of the phenazine oxidase mimics. ETS‐NOCV (extended transition state‐natural orbitals for chemical valence) plots of the reactive intermediates portray the coordination‐driven depletion of electron density from the nitrogens of OPD to cobalt center leading to the enhancement of electrophilic character on para‐positioned C‐atoms with respect to N‐atoms of OPD, therby catalyzing the nucleophilic attack by second OPD to produce the oxidation product, 2, 3‐diaminophenazine (DAP). Interestingly, we are able to isolate the oxidation product of the OPD oxidation reaction as a hydrated chloride salt, DAPH + Cl − ·3H2 O (2 ). The crystal engineering perspectives of 2 attribute the intriguing fate of the secondary chlorides for the stabilization of the oxidation product in crystalline phase. Abstract : This work envisions the synthesis, structural characterization, computational studies, and biomimics of the phenazine oxidase activity of a cobalt (III)‐dipyridyl amine complex under an ambient condition with successful isolation of the OPD oxidation product in single‐crystalline phase as a hydrated phenazine chloride salt.